Innovative training methods in business higher education - Árváné Ványi, Georgina; Gál, Tímea; Nábrádi, András; Csapó, Zsolt; Pető, Károly (Applied Studies in Agribusiness and Commerce, 2013)
A unique business-oriented educational method was launched in 2010 at the University Of Debrecen, Hungary, in the Faculty Of Applied Economics and Rural Development; the method has existed in the JAMK University of Applied Science in Jyväskylä (Finland) since 1993, and is called Team Academy. The gist of this training is that the students learn entrepreneurship through their ‘living’ organisations with the application of the principle ‘learning-by-doing’. Besides developing the students’ entrepreneurial competencies and skills, this educational model also offers team coaching tools to develop teams of 12-13 students that can cooperate in an efficient way. The key point of Team Academy, which has been launched in several European higher education institutes over the past years (e.g. Spain, France, the Netherlands, etc.), is that the most efficient way of learning how to operate a successful company is to learn it in practice. During the professional and project trainings, the cooperation of the team and their company’s efficiency is continuously developing with the help of team coaches. A quite wide variety of team coaching tools is used in this system, e.g. 360◦ evaluation, which is a very important tool of human resource management. Feedback from students also plays an important role in developing team cooperation; the professional frame for this is also given by the above-mentioned methodology. This method is used successfully at the Debrecen Team Academy which / and (do you mean that the a) Team Academy or b) the above-mentioned methodology will be presented? If B), then write ‘and’ instead of ‘which’) will be presented in this study. A database of 150 questionnaires is analysed through qualitative research methods.